Design of low power and high speed FFT/IFFT processor for UWB system - LIU Liang; WANG Xue-jing; YE Fan; REN Jun-yan (Tongxin xuebao)
A new 128/64-point FFT/IFFT processor used in Ultra-Wide-Band（UWB） system was presented.The proces-sor,which is based on 8×8×2 mixed radix algorithm,can deal with multiple inputs more efficiently for MIMO applica-tions.A new eight-path-feedback structure,which can provide a higher throughput and lower power dissipation,was proposed.The test chip has been fabricated using SMIC 0.13μm single-poly and eight-metal CMOS process with a core area of 1.44mm2.The throughput of this chip is up to 1Gsample/s,and the power dissipation is 39.6mW when it works at the throughput of 500Msample/s which meets the UWB standard.This chip reduces 40% of core area and saves 45% of power dissipation compared with those existing 128-point FFT processors.